Ecological Reconciliation: Laudato Si' Ecological Conversion as a Framework for Sustainable Development of IKN Nusantara - Andreas Jimmy; Yustinus Dwi Andriyanto; Emilianus Sember Sawo (SEAN Institute, 2023)
This study examines the gap between the ecological vision in the Laudato Si' encyclical and the development practices of Indonesia's new capital city (IKN) Nusantara, focusing on the application of the concept of ecological conversion in large-scale development. Through critical analysis of relevant literature and documents, the study identifies six main gaps, including the approach to economic growth, community participation, the relationship with nature, the role of technology, the scale of development, and the integration of spiritual values. The study also explores the challenges of implementing ecological conversion on a large scale and how to balance economic and environmental needs. The results show a significant difference between the holistic vision of Laudato Si' and conventional development practices, concluding that the implementation of ecological conversion requires a fundamental transformation in the understanding of development, progress, and humanity's relationship with nature.